Health visiting and safeguarding children: A perfect storm?. (2nd May 2019) - Peckover, Sue; Appleton, Jane V
Abstract : Health visitors play an important role in safeguarding and protecting children. In this article we review current research evidence and professional literature about this aspect of health visiting and highlight some of the practice challenges in undertaking this work. Three critical issues are discussed: the invisibility and unquestioned nature of much health visiting safeguarding work; that health visitors with their clinical expertise and accepted home visiting role are well placed to undertake this type of work; and the challenges of ensuring effective safeguarding within the context of economic austerity. The article highlights the important contribution of contemporary health visiting to safeguarding children and child protection. It is important that this role is made explicit to those commissioning health visiting services for children in the early years.